The role of differentiated instruction in the inclusion of students with special educational needs in English as a foreign language in Loja - Jiménez Ordoñez, Hilda Lucía (2025)
Effective integration of students with special educational needs (SEN) in English as a foreign language (EFL) class remains a major obstacle in Loja, where traditional teaching methods often fail to meet the diverse needs of students. This study explores differentiated instruction in the inclusion of students with special educational needs in English as a foreign language class in Loja. It aims to describe EFL teachers' perceptions about the effectiveness of DI in supporting the inclusion of students with SEN and to identify the barriers teachers face in implementing it. This study is descriptive in nature and used a mixed-method approach to collect data from English teachers in Loja; the research instrument was a questionnaire that encompassed qualitative and quantitative information of the implementation of differentiated instruction in English classrooms. On the one hand, for quantitative analysis, the data collected were analyzed using descriptive statistics; on the other hand, for qualitative analysis, thematic analysis was used to recognize trends among teachers' responses. Results indicated that, in general, teachers perceived differentiated instruction as an effective inclusion strategy, regularly adapted their teaching methods, and provided personalized feedback. However, lack of assistive technology, limited resources, large class sizes, and time constraints hindered its implementation. In addition, the results suggest that teachers have varying degrees of confidence in their ability to apply differentiated instruction. These findings suggest that effective implementation of differentiated instruction requires systematic institutional support, improved teacher training programs, and the development of context-specific resources